1961
DOI: 10.1037/h0047286
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radical hippocampal ablation on acquisition of avoidance response.

Abstract: The behavioral effects of bilaterial lesions in the hippocampal formation are not clear-cut. Such lesions have not hindered the formation of "conditioned emotional responses" in the rat (Brady & Hunt, 1955) nor altered the acquisition rate of avoidance responses in the cat (Brady, Schreiner, Geller, & Kling, 1954). Recently, Kimura (1958) reported that lesions in posterior hippocampus produce adverse effects in the learning of a rather unusual avoidance response. Lesions of similar size in anterior hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
110
3

Year Published

1964
1964
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(133 citation statements)
references
References 8 publications
20
110
3
Order By: Relevance
“…As was demonstrated by our test procedure, the location detection circuit of Figure 3 can be placed across small passages to record the direction of movement across a line, as in shuttling experiments (e.g., Isaacson, Douglas, & Moore, 1961;Randall & Riccio, 1969). If this pellets were made available from a food hopper located in a holding cage adjacent to the open-field room (Figure 2, bottom panel).…”
Section: Resultsmentioning
confidence: 99%
“…As was demonstrated by our test procedure, the location detection circuit of Figure 3 can be placed across small passages to record the direction of movement across a line, as in shuttling experiments (e.g., Isaacson, Douglas, & Moore, 1961;Randall & Riccio, 1969). If this pellets were made available from a food hopper located in a holding cage adjacent to the open-field room (Figure 2, bottom panel).…”
Section: Resultsmentioning
confidence: 99%
“…Isaacson, Douglas, and Moore (1961) showed that hippocampectomized rats, when compared with cortically ablated or unoperated controls, exhibited a greater resistance to extinction in an active avoidance situation. Kimble (1967) reported similar results in a Y maze.…”
Section: Modelmentioning
confidence: 99%
“…acquisition deficits were found on these Representative seetions were stained with two problems following hippocampal cresyl violet, Luxol fast blue, and lesions, especially because earlier hematoxylin and eosin. 3 investigators have not reported acquisition RESULTS deficits by hippocampal animals (Hunt & The Ss of Group 1 had large portions of Diamond, 1954; Isaacson, Douglas, & the pyriform cortex and Ammon's horn Moore, 1961;Teitelbaum, 1964;Webster & ablated. Except in Animal5, there were no Voneida, 1964).…”
Section: A a Buerger2 Comellmentioning
confidence: 99%